The effect of the cation aromaticity upon the thermophysical properties of piperidinium- and pyridinium-based ionic liquids - Bhattacharjee, Arijit
Experimental data on density, viscosity, refractive index and surface tension of four ILs: 1-Methyl-1-propylpiperidinium bis(trifluoromethylsulfonyl)imide [C(3)C(1)Pip][NTf2], 1-Butyl-1-methylpiperidinium bis(trifluoromethylsulfonyl)imide [C(4)C(1)Pip][NTf2], 3-Methyl-1-propylpyridinium bis(trifluoromethylsulfonyl)imide [C3C1Py][NTf2] and 1-Butyl-3-methylpyridinium bis(trifluoromethylsulfonyl)imide [C4C1Py][NTf2] were measured in the temperature range between 288.15 and 353.15 K and at atmospheric pressure to evaluate the impact of the cation's aromaticity upon the thermophysical properties of ionic liquids. The properties investigated show that the pyridinium aromatic ring, with its pi-pi interactions, leads to a more rigid, compact and organized liquid phase, while the less rigid structure of the piperidinium cation induces more entanglement and consequently higher resistance to shear stress (higher viscosities) and better surface arrangement (higher surface tensions). The group contribution methods proposed by Gardas and Coutinho were also evaluated and fitted to the experimental data, allowing the proposal of new parameters for the cations investigated. (C) 2014 Elsevier B.V. All rights reserved.